Between visit variability of thermal imaging of feet in people attending podiatric clinics with diabetic neuropathy at high risk of developing foot ulcers. (2nd September 2019) - Macdonald, Audrey; Petrova, Nina; Ainarker, Suhail; Allen, John; Lomas, Clare; Tang, Wegin; Plassmann, Peter; Whittam, Aaron; Bevans, John; Ring, Francis; Kluwe, Ben; Simpson, Rob; et al.
Abstract: Objective : People with diabetic neuropathy who have previously ulcerated are at high risk of re-ulceration. They should regularly attend podiatry clinics for surveillance and routine protective podiatric treatment. It has been suggested that inflammation prior to skin breakdown shows up as a hotspot on a thermal image even in the absence of clinical signs. The aim of this study is to quantify inter-patient and intra-patient thermal variations presented by diabetic feet at high risk of ulceration. Approach : Whole foot and spot temperatures were recorded for 96 patients who attended two successive podiatry appointments without ulceration 28 [28, 31] days apart, median [interquartile range]. This was a part of a longer study into whether thermal imaging in clinic can reduce the rate of re-ulceration. Main results : The variation in spot temperature right/left differences for single patients between visits was comparable to the variation observed between patients (0.8 [0.3, 1.5] °C compared with 0.9 [0.4, 1.7] °C). Similarly, whole foot temperature variation for a single patient between visits was comparable to the variation observed between patients (0.6 [0.2, 1.1] °C compared with 0.8 [0.2, 1.3] °C). Significance : Thresholds which depend on thermal differences from visit to visit are unlikely to have sufficient specificity to effectively target treatment designed to prevent the development of foot ulcers.